Focused logistics: holy grail or poisoned chalice? - Moore, David M.; Antill, Peter D. (Taylor & Francis, 1999)
With logistics having become more important as the 20th century has progressed, and particularly since the end of the Cold War, the need for more efficient and effective logistics is becoming paramount, as it is seen as both a 'competitive advange' and a 'force enabler'. 'Focused Logistics' is the latest term to enter usage, and this paper will examine how different it is from what has gone before, and whether it is applicable to some of the operational challenges that the armed forces might face in the near future.